MODERN TRENDS IN MARKETING PRICING AND THEIR IMPACT ON DEMAND - LAGODIIENKO, Volodymyr; MILCHEVA, Viktoriia; GOLODONIUK, Olga; BRAIKO, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article is dedicated to the study of modern trends in marketing pricing and the analysis of its impact on consumer demand. The purpose of the article is to analyze, systematize, and improve the existing theoretical and methodological foundations of marketing pricing and to investigate the impact of modern pricing approaches on consumer demand in a changing economic environment.The article examines the role of marketing pricing in modern conditions of fierce competition, where pricing becomes not only a tool for setting prices but also an important element of strategic management for businesses. The study presents an analysis of the main functions of marketing pricing and their impact on long-term company goals, particularly on maintaining competitive positions, building customer loyalty, and achieving financial results. It is found that a well-chosen pricing strategy allows companies to adapt to market changes, introduce innovations, and maintain high demand for their products or services. The study substantiates that marketing pricing is a strategic tool that helps businesses not only satisfy customer needs but also optimize profitability by creating additional consumer value. The main pricing approaches are presented, such as value-based pricing, competitive pricing, psychological pricing, dynamic pricing, and personalized pricing, which allow businesses to build an effective pricing strategy considering market specifics and customer needs. The research reveals that in the context of digitalization, the use of analytical tools and big data significantly increases the accuracy of pricing, enabling companies to better forecast demand changes, adjust prices in real-time, and create personalized offers for customers. In the era of digital technologies, pricing becomes more flexible and adaptive, ensuring profit maximization and increased market competitiveness. It is substantiated that marketing pricing is an essential element of a company’s strategy, which helps not only achieve financial goals but also fosters the formation of stable long-term relationships with customers. In today’s business environment, a successful pricing strategy is a key factor that allows businesses to retain customer loyalty, attract new clients, and ensure stable market growth.
Keywords: marketing pricing; pricing strategy; competitiveness; consumer loyalty; demand; digitalization